STEM AND BLENDED LEARNING FOR ENHANCING CRITICAL THINKING AND COLLABORATION - Shahina Shukhratova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article explores the integration of STEM (Science, Technology, Engineering, and Mathematics) education with blended learning approaches to enhance critical thinking and collaboration among students. By reviewing existing literature and employing a mixed-methods research design, this study identifies effective strategies and methodologies for implementing blended learning in STEM classrooms. The findings indicate that blended learning environments foster deeper engagement, promote collaborative problem-solving, and enhance critical thinking skills. This paper concludes with recommendations for educators and policymakers to support the adoption of blended learning in STEM education.